The Impact of Youtube English Videos on Students’ Listening Comprehension Skills at Senior High School in Gowa - Endang Novita Efruan; Sukmawati; Muhammad Yahrif; Deddy Yusuf (CV. Eureka Murakabi Abadi, 2023)
Technological developments in this modern era have made many people accustomed to using technology that is fast and easily accessible anywhere as an information space, especially in the world of technology. One of the information technologies used by researchers in this research is online social media, namely the YouTube application media. This research aims to determine the impact of YouTube English videos on students' listening skills at SMA Negeri 10 Gowa. This research is quasi-experimental research using the Control class and the Experiment class. The sample for this research consisted of 30 Experiment class students and 30 Control class students at SMA Negeri 10 Gowa. The results of this research show that the post-test results for the Experiment class have an average score of 78.50 and the pre-test is 69.07, while the post-test for the Control class has an average score of 51.57 and the pre-test is 34.97. The results of the data were analyzed using the Paired t-test, which showed that Sig. (2-tailed) was 0.000 lower than 0.05 so that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. These results show the Impact of YouTube Videos on Listening Skills Student. Based on the results of this research, it can be concluded that the YouTube application media is effective and has an impact on the listening skills of class X SMA Negeri 10 Gowa.